Penggunaan Multimedia Interaktif Pada Pembelajaran Matematika Siswa Sekolah Dasar; Systematic Literatur Review - Oktania, Sella; Juansah, Dase Erwin; Rosmilawati, Ila (LPPM Universitas Bina Bangsa, 2025)
This study aims to systematically review various scientific literature on the use of interactive multimedia in mathematics learning in elementary schools in the 2020–2025 period. The method used is the Systematic Literature Review (SLR) with the PRISMA method consisting of four main stages, namely: Identification, Screening, Eligibility, and Included from various trusted sources such as Google Scholar, ScienceDirect, and DOAJ. Of the 50 articles identified, 15 articles met the inclusion criteria and were further analyzed. The results of the various studies analyzed showed that the use of interactive multimedia can increase learning motivation, understanding of mathematical concepts, and students' academic achievement. Multimedia also helps foster students' curiosity and self-confidence because of the instant feedback and concrete visualization of concepts. This study recommends the integration of interactive multimedia designed according to the age and curriculum needs of elementary school students.